Commentary on the judgment of the Constitutional Tribunal of 3 July 2025, case U 2/25 (Discourse of Law and Administration, 2026)
The gloss analyzes the judgment of the Constitutional Tribunal of 3 July 2025, file reference U 2/25, in which it was found that the regulation of the Minister of Education regarding the organization of religious education classes is inconsistent with the Constitution of the Republic of Poland and the Act on the Education System due to the lack of the required “agreement” with churches and other religious associations, which violated Article 12, paragraph 2 of the Act and Article 25, paragraph 3 of the Constitution. The judgment –   if published – would lead to a return to the 1992 regulation, which stipulated two hours of religious education per week, and the author of the commentary points out that the Tribunal limited itself to an analysis of procedural irregularities, without assessing the substance of the reduction in the number of hours. Against the background of this assessment, there also arises the problem of distinguishing the concept of “agreement” from “consent”, which is of fundamental importance for the scope of permissible changes in the implementing provisions concerning religious education. The significance of the ruling for consolidating the model of religious education, the role of churches and other religious associations, and the limitation of administrative freedom was emphasized, and the controversy surrounding the legitimacy of the current composition of the Tribunal was also noted. The author assesses the judgment as excessively formalistic and points out that issues of religious education should be resolved in the legislative process, preceded by a democratic public debate, and not solely through constitutional review, emphasizing the importance of observing procedures for the rule of law and the difficulties in reforming education in the context of freedom of conscience and parents’ rights.
Keywords: Constitutional Tribunal; Constitution of the Republic of Poland; religious education; freedom of conscience and religion; agreement between the state and churches and other religious associations